A water-soluble inclusion complex of pedunculoside with the polymer β-cyclodextrin: a novel anti-inflammation agent with low toxicity. - Chang Liu (Public Library of Science (PLoS), 2014)
More than 50% of new drug candidates in drug discovery are lipophilic and exhibit poor aqueous solubility, which results in poor bioavailability and a lack of dose proportionality. Here, we improved the solubility of pedunculoside (PE) by generating a water-soluble inclusion complex composed of PE and the polymer β-cyclodextrin (CDP). We characterized this novel complex by 1H NMR, FT-IR, UV-vis spectroscopy, powder X-ray diffractometry and thermogravimetric analysis. The ratio of β-cyclodextrin (β-CD) units in CDP to PE was determined to be 2∶1. The KD value of the inclusion complex was determined to be 4.29×10(-3) mol•L(-1). In contrast to the low solubility of PE, the water-solubility of the PE-CDP complex was greatly enhanced. A preclinical toxicological study indicated that PE-CDP was well tolerated for a single administration. Importantly, the anti-inflammation potency of the PE-CDP complex was higher than that of PE. As a result, the formation of inclusion complexes by water-soluble CDP opens up possible aqueous applications of insoluble drug candidates in drug delivery.